BENEFITS OF LEARNING A SECOND LANGUAGE - Ahmadjonova Zulhumor Mo’minjon Qizi; Umaraliyeva Munojat Mashrabovna (Лучшие интеллектуальные исследования, 2024)
Abstract.Learning a second language offers numerous benefits, including improved cognitive abilities, better working memory, and traveling and a greater understanding of different cultures. In addition to cognitive benefits, learning a second language can also open up enhanced career opportunities. In today's globalized world, being bilingual is a valuable skill that can make individuals more competitive in the job market. Many employers value employees who can communicate with clients and colleagues in multiple languages, especially in industries such as business, tourism, and international realitions. This article explores the advantages of learning a second language and how it can positively impact individuals in various aspects of their lives.